Penguatan Peran Takmir Masjid dalam Tanggap Bencana Gempa Bumi di Desa Bangunharjo - Muthmainnah Muthmainnah; Toto Hermawan; Suryanto Suryanto; Indra Suharyanto; Abdul Mughits; Akhmad Muhaini (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
The purpose of implementing community service is to encourage active participation of mosque takmirs in Bangunharjo Village, Sewon District, Bantul Regency to strengthen their role in handling tectonic earthquakes, especially mitigation. For this reason, activities are directed at enriching knowledge and technology about reducing the impact of earthquakes on the community in a sustainable manner by mosque leaders and administrators so that their role can be effective in mitigation activities. The appropriate participatory approach is an option in carrying out debriefing to motivate mosque administrators to be fully involved in mitigation activities as well as readiness to act and coordinate when an earthquake occurs. Important notes from the community that can be followed up are, among others, the need for assistance is very real, especially from information and technology in handling earthquake problems and strengthening socialization in the form of a curriculum that is more permanent and easy to implement in mosques, especially for children studying in TPA and congregation recitation. This segmentation is expected to be the success of disaster mitigation programs, especially those relating to earthquake mitigation issues related to the religious sector.